Ceramic and food consumption in ancient northern Ethiopia: Analysis of organic residue in pottery from Yeha by GC-MS - Polla, Silvia; Japp, Sarah; Köster, Marlene; Stukenbrok, Heiko; Springer, Andreas; La Piana, Giuseppe (Journal of Global Archaeology, 2024)
This study applies chemical analyses by GC-MS (gas chromatography-mass spectrometry) of, on the one hand, absorbed residue in vessels and, on the other hand, of vessel fill contents in order to investigate the use and function of pre-Aksumite pottery from the excavations of the German Archaeological Institute in Yeha and Melazo, and to draw conclusions about consumption, dietary habits and cooking traditions in the ancient Ethiopian highlands. The results of the analyses show fermentation markers of fruits and markers for plant and animal fats, with a slight dominance of plant-based consumption for a set of small pots suitable for serving food. A notable feature is the potential identification of moringa seed oil as content of a storage vessel from the palace in Yeha. In order to identify the contents more precisely, targeted research is necessary, which requires better knowledge of ancient raw materials available in the region. The current results provide initial clues for further investigations.